Influence of denture treatment on brain function activity - Toshio Hosoi; Masakazu Morokuma; Naoyuki Shibuya; Yoshikazu Yoneyama (Elsevier, 2011)
The objective of the present study was to clarify whether the treatment of complete dentures and the use of partial dentures influence brain function activity as determined by electroencephalograms (EEG). Eighteen complete and twenty partial denture wearers participated in the study. In order to evaluate denture function, the occlusal contact area and occlusal force were measured using a Dental Prescale Occluzer®. To evaluate brain function activity, EEG data obtained employing ESA-pro were analyzed using DIMENSION. The occlusal contact area significantly increased after complete denture treatment in all 18 subjects and significantly increased with wearing partial dentures in all 20 subjects. The occlusal force of complete and partial denture subjects significantly increased. An increase in brain function activity was noted in 14 of the 18 complete denture wearers, and after gum chewing with dentures in the 20 partial denture wearers. In this study, it was revealed that brain function activity was enhanced by the improvement of complete dentures, and by wearing partial dentures. Not only denture function improvement but also brain functional activation was achieved in elderly denture wearers at risk of brain activity deterioration.